ESTERIFICATION REACTION KINETICS OF THE MANUFACTURING OF ESTERS BASED LUBRICANT - Camellia S.P., Evieta
Lubricants are high viscosity oils that are used to form a separating layer between surfaces made of metal that touch and move. Mineral oil is the raw material most commonly used to make lubricants. However, mineral oil based lubricants can cause environmental pollution. An alternative to mineral oil is vegetable oil. Lubricants that are made from vegetable oils are called biolubricants. Biolubricants have disadvantages, namely low oxidative stability, and unfavorable low temperature fluidity. This is due to the presence of ?-hydrogen in the glycerol molecule. Glycerol can be replaced with polyols which do not have ?-hydrogen such as Trimethylolpropane (TMP). In this study, an esterification reaction experiment was carried out using oleic acid (OA) and trimethylolpropane (TMP) with a concentration ratio of TMP:OA (3:1), using a 3.5%-w PTSA catalyst and carried out at a temperature variation of 140-180oC. From the experiment, it was found that the higher the temperature, the higher the oleic acid conversion value in the esterification reaction with the maximum conversion value of 79.4% at 180oC. From the experiment it was also determined that the esterification reaction for making biolubricant is a fourth order reaction with an activation energy value of 48644 J/mol. The biolubricant product obtained have an acid number in the range of 6-13 mg-KOH/g, and a kinematic viscosity value (at 40oC) of 878.75-1928.75 cSt making the final product classified as ISO VG 1000 and ISO VG 1500 lubricant.